Clinical and Epidemiological Features of Stroke in the Fergana Valley - Mamatalieva Janona Alimjanovna (Central Asian Journal of Medical and Natural Science, 2022)
This article presents a comparative analysis of the clinical-epidemiological features of stroke. Diseases of the brain, blood vessels-one of the pressing medical and social problems, is the leader in the level of disease stocking and mortality in economically developed countries. Vascular diseases and especially heart diseases are also important medical and social problems in Uzbekistan. This is determined by the primary disability associated with the disease and the high mortality rate.